Porphyromonas gingivalis survival skills: Immune evasion - Zheng, Shaowen; Yu, Shiwen; Fan, Xiaomiao; Zhang, Yonghuan; Sun, Yangyang; Lin, Li; Wang, Hongyan; Pan, Yaping; Li, Chen (Journal of periodontal research, 2021)
Periodontitis is a chronic inflammatory condition that destroys the tooth‐supporting tissues and eventually leads to tooth loss. As one of the most prevalent oral conditions, periodontitis endangers the oral health of 70% of people throughout the world. Periodontitis is also related to various systemic diseases, such as diabetes mellitus, atherosclerosis, and rheumatoid arthritis, which not only has a great impact on population health status and the quality of life but also increases the social burden. Porphyromonas gingivalis (P. gingivalis) is a gram‐negative oral anaerobic bacterium that plays a key role in the pathogenesis of periodontitis. Porphyromonas gingivalis can express various of virulence factors to overturn innate and adaptive immunities, which makes P. gingivalis survive and propagate in the host, destroy periodontal tissues, and have connection to systemic diseases. Porphyromonas gingivalis can invade into and survive in host tissues by destructing the gingival epithelial barrier, internalizing into the epithelial cells, and enhancing autophagy in epithelial cells. Deregulation of complement system, degradation of antibacterial peptides, and destruction of phagocyte functions facilitate the evasion of P. gingivalis. Porphyromonas gingivalis can also suppress adaptive immunity, which allows P. gingivalis to exist in the host tissues and cause the inflammatory response persistently. Here, we review studies devoted to understanding the strategies utilized by P. gingivalis to escape host immunity. Methods for impairing P. gingivalis immune evasion are also mentioned.